OBSTACLES IN BRAZILIAN SCIENCE: AN EXPERIENCE REPORT (REMUNOM, 2023)
This article is a descriptive experience report carried out in 2023. This experience report aims to describe the experiences in the position of evaluator in multidisciplinary events in the health area, held in Brazil, whose function was to evaluate full articles, simple abstracts and book chapters submitted online without identifying the responsible authors. The evaluation of the articles took place in the first semester of 2023, and the insertion in the position of evaluator took place through public notices and invitations. The papers evaluated came from different health sectors: medicine, physiotherapy, speech therapy, nutrition, nursing, occupational therapy, physical education, veterinary medicine and psychology.